Human rights, culture and context : anthropological perspectives - Wilson, Richard, 1964- (Anthropology, culture, and society., 1997)
"A world characterised by ethno-nationalist struggles, civil wars, and political violence has led anthropologists to examine in more detail the relationships between state violence, ideas about 'culture', and the activities of human rights organisations. The first coherent contextual study of its kind, Human Rights, Culture and Context moves beyond the conventional anthropological dichotomy of universalism versus cultural relativism by considering recent theoretical insights into the politics of identity and by tracing the concrete interconnections created by a globalisation of human rights." "Drawing on case studies from around the world - Guatemala, Mauritius, Hawai'i, Iran, the United States and Mexico - this collection documents how trans-national human rights discourses and legal institutions are materialised, imposed, resisted and trans-formed in a variety of contexts."--Jacket